A theater without theater - Plasencia, Clara (Barcelona : Grup 3., 2007)
A theater without theater : the place of the subject / Manuel J. Borja-Villel ##A theatre of operations : a discussion between Alain Badiou and Elie During ##Playground / Patricia Falguières ##What's happening, man? : Interview with Jean-Jacques Lebel / by Bernard Blistène##Actors, situations, outcomes : theater machine and theater : subaltern stages in the Spanish state / Pedro G. Romero##Introduction to the itinerary / Bernard Blistène and Yann Chateigné##Itinerary##James Coleman : so different...and yet, 1980 / Bernard Blistène ##Glossary / Marc Dachy##Chronology (1896-1989) / Anne Stenne.
boek